Appraisal of Sand and Gravel Quarrying Operations in Southern Negros Occidental for Promotion of Extractive Industry Transparency Initiative in the Philippines - DAGUNAN, Mary Ann S. (Journal of Environmental Management and Tourism, 2022)
The study was conducted to assess the status of sand and gravel quarrying operations in Southern Negros Occidental for promotion of extractive industry transparency initiative in the Philippines. Specifically, this sought to determine the number of quarry operators with approved permits and applicants, the source and volume of extraction, the validity of permits, ground validation of maps, and the collection of issues and concerns about sand and gravel quarrying.The collected data was summarized and analyzed using descriptive statistics such as means, frequencies, and percentages.Spatial data verification,on the other hand, was carried out using a handheld global positioning system device. According to the findings, the extracted sand and gravel were used for industrial and commercial purposes. A total of 73.47 hectares were obtained from various sources. Approximately 200 of 738 applications were approved, with an allowed maximum extraction volume of 432,600 cubic meters. Data also show that a substantial amount of sand and gravel are extracted in the Cauayan, Sipalay, Ilog, and Hilabangan rivers.The most common problems and issues identified were destruction of river banks, landscapes and croplands and failure to disseminate proper information during public hearings or community consultations.Quarry operators have had to deal with issues such as environmental study compliance, costly road rights of way, accretion along river banks, and required road rights of way payments.